PENGARUH DOSIS DAN LAMA PERENDAMAN TELUR AYAM DALAM LARUTAN DAUN SALAM TERHADAP KANDUNGAN KOLESTEROL - Prihastutik Tintawati; Nur Kholis (Universitas Islam Kadiri, 2017)
The purpose of this research was to find the influence of doses and period of soakingin Bay Leaf Solution to Cholesterol Contain of Chicken Egg.Research carried out in Animal Husbandry Laboratories, Faculty of Agriculture, Kadiri Islamic University at 20-26 july 2013. The cholesterol analysis was done in Laboratory of chemistry, MIPA Faculty, UMM starting on july 27 - august 12 2013 Material used was 144 egg which 1 day old with eggs weight between 40-49 gram taken off the farm laying chicken.The methodology used is the method factorials Complete Random Design (RAL).The first factors was doses of bay leaf, consisting of 4 level: D0: control (without treatment); D1: soaking in 5%solution leaf; D2: soaking in7.5%solution leaf %; D3: soaking in 10%solution leaf.The second factor was period of soakingconsisting 2 level: L0: control (without treatment); L1: soaking in leaf solution for 3 days; L2: soaking in leaf solution for 6 days.To achieve 12 combination treatment, where treatment repeated three times, every second egg used 4.The total number of eggs needed the research was 144 egg The result showed that the influence of doses and period of soaking in bay leaf solution as regards of cholesterol content on eggs chicken show an significant influence interaction (p<0,01).The cholesterol content of egg (mg/100g) on each combination treatment was: D0L0= 282,857 ± 14,1374a ; D0L1= 273,743 ± 9,3158a ; D0L2 = 262,404 ± 7,9843bc ; D1L0 = 286,089 ± 4,2407a ; D1L1 = 261,148 ± 6,0831c ; D1L2 = 249,412 ± 5,8339de ; D2L0 = 283,247 ± 3,9063a ; D2L1 = 243,644 ± 3,1968e ; D2L2 = 227,360 ± 5,1087g ; D3L0 = 281,548 ± 3,2804a ; D3L1 = 229,643 ± 2,6179fg ; D3L2 = 200,271 ± 4,0193h. The conclusion of this research was that treatment of bay leaf solution, period of storage and significant combination (p<0.01) against eggs cholesterol.Advice from this research was used a combination of better treatment 10% doses and period of soaking in a solution of bay leaf in 6 days to get low cholesterol content of chicken egg. The further research of organoleptic test needed to determine the preference of consumers with this kind of eggs.